Analisis Perlakuan Akuntansi Aset Tetap Pada PT Prima Indonesia Logistik Berdasarkan PSAK No 16 - Tessa Anggraini; Laylan Syafina (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
PT Prima Indonesia Logistik is a subsidiary of a State-Owned Enterprise (BUMN), which is engaged in logistics services operating in Belawan. To be able to achieve the company's goals that have been set, companies need various production factors to support and facilitate operational activities, namely fixed assets. The purpose of this study was to determine whether the accounting treatment of fixed assets at PT Prima Indonesia Logistik was in accordance with the Statement of Financial Accounting Standards No. 16. In writing this study, the nature of the research used was case study. With this method, the facts regarding the accounting treatment policy for tangible fixed assets are obtained by observing and analyzing a research object problem that occurs in a research location on the existing suitability and then draws conclusions from the problems studied. After conducting research, the authors obtained the results that the company's policy in accounting treatment of fixed assets is still not in accordance with PSAK No. 16. Therefore, companies must consider many things in making policies on recording the acquisition price of fixed assets, expenses after the acquisition of fixed assets, depreciation fixed assets, as well as the presentation of fixed assets in the financial statements.